2019
DOI: 10.1021/acs.est.9b04369
|View full text |Cite
|
Sign up to set email alerts
|

DEHP and DINP Induce Tissue- and Gender-Specific Disturbances in Fatty Acid and Lipidomic Profiles in Neonatal Mice: A Comparative Study

Abstract: Di-isononyl phthalate (DINP) is considered one of the main industrial alternatives to di­(2-ethylhexyl)­phthalate (DEHP), a well-known chemical with various toxic effects including the disruption with lipid metabolism. However, the potential effects of DINP on lipid metabolism have rarely been investigated in mammals. Our study demonstrated that exposure of neonatal mice to DEHP and DINP at a daily dose of 0.048 or 4.8 mg/kg from postnatal day 0 (PND0) to PND21 caused nonmonotonic as well as tissue- and gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Mass spectrometer parameters were set as follows: CUR: 25 psi, IonSpray voltage: 5500 V, TEM: 350 °C, GS1:30 psi, GS2:30 psi. The MRM information referred to our previous method with some modifications, and the details are given in Table S2. Lipid annotation was based on our previous and other methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass spectrometer parameters were set as follows: CUR: 25 psi, IonSpray voltage: 5500 V, TEM: 350 °C, GS1:30 psi, GS2:30 psi. The MRM information referred to our previous method with some modifications, and the details are given in Table S2. Lipid annotation was based on our previous and other methods.…”
Section: Methodsmentioning
confidence: 99%
“…The MRM information referred to our previous method with some modifications, and the details are given in Table S2. Lipid annotation was based on our previous and other methods. Concentrations of each lipid species were calculated by relating the peak areas of each species to the peak area of the corresponding internal standard using Analyst 1.6.3 software (AB Sciex, U.S.A.), and normalized by wet weight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the phosphopantetheinyl portion of CoA is a crucial component of acyl carrier protein, essential for the biosynthesis of fatty acid and lipid metabolism [23]. In our study, some lipids and lipid-like molecules were identified as core elements, these affected lipid metabolism mainly contain the general functions of energy storage, cell membrane composition and signal transmission and molecular recognition processes [24][25][26]. Fullerene nanoparticles stimulated the release of arachidonic acid from clownfish cells and arachidonic acid (AA) from membrane phospholipids via phospholipase A2S, which may be related to the pathophysiological events [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro and in vivo experiments confirmed that MEHP as an active compound can have impact on lipolysis and glycolysis metabolism, resulting in lipid accumulation. The possible mechanisms of MEHP-induced lipid metabolism dysregulation may be due to its capability in inhibiting the Janus kinase 2-signal transducer and activator of the transcription protein 5 (JAK2/STAT5) pathway, working as the agonist of peroxisome proliferator-activated receptor gamma (PPAR-γ) and disturbing the mitogen-activated protein kinase (MAPK) pathway . It was well known that the JAK2/STAT5 signaling pathway is involved in lipogenesis, and PPAR-γ participates in regulating the expression of cellular lipids .…”
Section: Introductionmentioning
confidence: 99%